2001
DOI: 10.1164/ajrccm.163.2.2006031
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Necrosis Factor α Gene Promoter Polymorphism with the Presence of Chronic Obstructive Pulmonary Disease

Abstract: Tumor necrosis factor alpha (TNF-alpha), a potent proinflammatory cytokine, may be involved in the development of chronic obstructive pulmonary disease (COPD). The production of TNF-alpha is elevated in the airways of these patients. A polymorphism at position -308 of the TNF-alpha gene promoter (TNF-alpha-308*1/2) is known to be associated with alteration of TNF-alpha secretion in vitro. In this study we examined the differences in TNF-alpha-308*1/2 allele frequency to investigate the association of this poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
2
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 18 publications
2
88
2
3
Order By: Relevance
“…When the present study was planned, it was debated whether inconsistent results in different populations with respect to association of TNF-308*2 allele with COPD was due to a bias related to heterogeneity of COPD patients. In fact, the paper by SAKAO et al [6] reported a positive association with Japanese COPD patients with chronic obstruction in whom a history of chronic bronchitis had been excluded, thus suggesting, even if not clearly stated in the paper, that those patients were mostly affected by emphysema. By contrast, a positive association with the TNF-308*2 allele was found in Taiwanese subjects meeting the criteria for chronic bronchitis [5].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…When the present study was planned, it was debated whether inconsistent results in different populations with respect to association of TNF-308*2 allele with COPD was due to a bias related to heterogeneity of COPD patients. In fact, the paper by SAKAO et al [6] reported a positive association with Japanese COPD patients with chronic obstruction in whom a history of chronic bronchitis had been excluded, thus suggesting, even if not clearly stated in the paper, that those patients were mostly affected by emphysema. By contrast, a positive association with the TNF-308*2 allele was found in Taiwanese subjects meeting the criteria for chronic bronchitis [5].…”
Section: Discussionmentioning
confidence: 91%
“…TNF-a levels are increased in sputum of COPD patients [37], and weight loss in COPD has been associated with increased levels of circulating TNF-a [38]. The potential implications of the two TNF-a and Lt-a polymorphisms investigated have already been extensively discussed [1][2][3][5][6][7][8][9]. In this article, for the first time, the authors have added the genetic study of two other TNF family members, TNFR1 and TNFR2, biologically reasonable candidates involved in mediating a number of TNF-a and LT-a effector functions [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α has been shown to correlate with body mass index (BMI) and cigarette smoke exposure [71,72] and other inflammatory mediators [73] in COPD. A polymorphism of the promoter region of the TNF-α gene has been implicated in the occurrence, severity, and mortality risk of COPD [74][75][76].…”
Section: Role Of Tnf-α In Asthma and Copdmentioning
confidence: 99%
“…Carriage of the TNF2 allele also conferred a higher risk to the development of chronic bronchitis in a Taiwanese population (Huang et al 1997). In the study by Sakao et al (2001), a significant relationship between the TNF1/2 allele frequency and the presence of smoking-related COPD in Japanese was revealed. Sakao et al (2002) subsequently assessed the extent of emphysematous changes in COPD patients using high-resolution CT scanning.…”
Section: Gene Polymorphisms Of Inflammatory Mediators In Relation To mentioning
confidence: 99%